Métodos de control postcosecha de la infección por el genero penicillium en cítricos, peras y manzanas - Campos Manzanedo, Fiorella Katherine (2015)
The present revision had at disclosing information about researches of methods of control post-harvest of the infection for the kind Penicillium citrus, pears and apples. The method of control that they give better worked out for the infection control for the kind they are Penicillium: Integrated control (physical systems and chemicals, physical systems and biological control, chemical systems and biological control ); Biological control ( with the application of antagonistic microorganisms ); Physical control ( modified atmospheres, controlled atmospheres, refrigeration, treatments with heat: Curing and hot water, application coatings: Commercial waxes and eatable coatings ); Also in the control post-harvest methods we have the chemical Control ( natural substances, natural additives and substances GRAS, fungicides of low risk ). These methods have become a viable option in the fruits protection against the infection caused by the kind Penicillium, the fact that they show up in the post-harvest, which originate a lot of economic losses.